PUTUSAN PENGADILAN NEGERI PADANG NOMOR: 69/Pdt.G/2009/PN.Pdg TENTANG HIBAH WASIAT PERSPEKTIF HUKUM ISLAM - Suci Rahmawati (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2019)
This article would explain the testament of the testamentary gift Number: 69/Pdt.G/2009/PN.Pdg., in the Padang District Court. As for the background of this research is the settlement of the will between the people of Islam, but decided by the district court, so there are some irregularities, both in terms of formal law and Islamic law. This research is a normative legal research with data analysis method in the form of content analysis. Based on the results of the decision are considered appropriate by the panel of judges who completed the case. Although there are no legal remedies from the parties against the decision of the district court judge, from the perspective of Islamic law the decision is still contrary to what should apply to people of Islam.